Canada. Significant achievements 2021 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Canada during 2021 are identified, with respect to the needs and interests of the country, strengthening issues of climate change, soil and water management, wet markets, food security in imports and exports, livestock reproduction, agrotourism, sustainable development, climate finance and microfinance. Likewise, work was done on the control of diseases, such as African swine fever (ASF), on resistance to herbicides and pesticides, on zoonotic risks in the Andes, and on dealing with the pandemic caused by COVID-19. Finally, work was done on the inclusion of rural women in agriculture and on the implementation of new technology, such as databases, educational platforms, blockchain, data science, the internet of things, and artificial intelligence.